Diagnóstico de la comunicación interna en la Dirección Provincial Agropecuaria de Zamora Chinchipe. Periodo tercer trimestre del año 2013. Propuesta alternativa - Márquez Ramírez, Ana Marisol (2014)
This thesis Entitled "Diagnosis of Internal Communication in the Provincial Agricultural Zamora Chinchipe. Period third quarter 2013.Propuesta Alternative" determines that the problem is manifested in not having an updated regulation or internal communication instructive ; this perspective was proposed to make a diagnosis to identify the situation of internal communication in the Provincial Agricultural , Zamora Chinchipe and propose a communication plan that allows for efficient communication processes within the institution , a communications proposal to position better way their corporate image to the public. Farmers ' organizations , organizational development, organizational assessment , organizational assessment , target communication communication, organizational vision of external communication , internal communication, types of communication tools : In the development of this research examined aspects internal communication ; these elements was considered a strategy to perform interactive internal communication plan for the Provincial Agricultural Zamora Chinchipe for Directing Staff , Administrative and Technical Institution. Through the use of surveys was reached to determine that the institution does not have an internal communication handbook for promoting the communication does not have a communication policy where they are located at the main tools of information within the systems of institutional intercom as objective to improve the functions and carry out the fulfillment of the mission and vision of the organization.